2023
DOI: 10.1021/acs.inorgchem.3c01330
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared LuCa2ScZrGa2GeO12:Cr3+ Garnet Phosphor with Ultra-broadband Emission for NIR LED Applications

Abstract: Near-infrared phosphor-converted light-emitting diodes (NIR pc-LEDs), as a new generation of NIR lighting sources, have wide prospects in the areas of food analysis and biological and night vision imaging. Nevertheless, NIR phosphors are still limited by short-wave and narrowband emissions as well as low efficiency. Herein, a series of NIR phosphors, LuCa2ScZrGa2GeO12:Cr3+ (LCSZGG:Cr3+), with broadband emissions have been developed and first reported. At 456 nm excitation, the optimized LCSZGG:0.005Cr3+ phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 57 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…According to the slope of the line, the hω and S values were determined to be 14.9 meV and 2.64, respectively, which indicated that Cr 3+ activators experienced a weak EPC effect in RLAF host. 46 This was also assumed to be the reason for the remarkable PL thermal stability of RLAF:Cr. Moreover, the QE of RLAF:0.02Cr upon excitation with a wavelength of 450 nm was found to be 77.7%.…”
Section: Resultsmentioning
confidence: 99%
“…According to the slope of the line, the hω and S values were determined to be 14.9 meV and 2.64, respectively, which indicated that Cr 3+ activators experienced a weak EPC effect in RLAF host. 46 This was also assumed to be the reason for the remarkable PL thermal stability of RLAF:Cr. Moreover, the QE of RLAF:0.02Cr upon excitation with a wavelength of 450 nm was found to be 77.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the maximum value of IQE is higher than those of most NIR materials when the emission peak is centered above 800 nm. This includes LuCa 2 ScZrGa 2 GeO 12 :Cr 3+ (λ em = 815 nm, IQE = 68.8%), La 2 MgZrO 6 :Cr 3+ (λ em = 825 nm, IQE = 58%), and LiScSi 2 O 6 :Cr 3+ (λ em = 845 nm, IQE = 64.4%). The AE and EQE values also increase with increasing Cr 3+ concentration. This can be attributed to the improved absorption of the incident excitation energy by the phosphor.…”
Section: Resultsmentioning
confidence: 99%
“…Room-temperature photoluminescence decay curves of Na 2 CaZr 2– x Ge 3 O 12 : x Cr 3+ ( x = 0.01, 0.02, 0.04, 0.06, 0.08, and 0.10) are presented in Figure d upon excitation with 460 nm light. All of the decay curves are described by a single-exponential function as presented in eq , I t = I 0 + A nobreak0em0.1em⁡ exp ( t τ ) where I 0 stands for the offset, I t represents intensity at time t , A represents the fitting constant, and τ is the lifetime. The obtained lifetime gradually decreases from 54.8 to 40.2 μs with increasing Cr 3+ concentration, stemming from the gradually enhanced interactions between Cr 3+ ions, which lead to energy loss in nonradiative transitions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the thermal stability is also a crucial factor for evaluating the potential of phosphors in practical applications. 55 The temperature-dependent PL spectra of the YGSAG:0.08Cr 3+ sample from 303 to 483 K with an interval of 30 K were collected, as depicted in Fig. 5a.…”
Section: Resultsmentioning
confidence: 99%